2023
DOI: 10.3389/fmed.2023.1088745
|View full text |Cite
|
Sign up to set email alerts
|

White blood cell count affects fetal fraction and test failure rates in noninvasive prenatal screening

Abstract: ObjectiveTo investigate the effects of white blood cell (WBC) count on fetal fraction (FF), which is an essential quality control for obtaining reliable results, and on the rate of screen failures in noninvasive prenatal screening (NIPS).MethodsNoninvasive prenatal screening, serum lipid and liver enzyme level measurements, and WBC count were performed for 4,281 pregnancies with male fetuses. After adjusting for confounders, including the maternal characteristics and alanine aminotransferase (ALT) levels, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Even though many risk factors for low FF have been described, there was still a subset of patients in our study with no obvious reason for LFF. In search for other factors affecting FF, recent studies showed a negative correlation between FF and IVF‐conception, elevated triglyceride levels, alanine transaminase levels and increased white blood cells 53–55 . It should be further investigated if systematic evaluation of these parameters would be useful in NIPT‐failures and if this would help the decision to perform a redraw or not.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though many risk factors for low FF have been described, there was still a subset of patients in our study with no obvious reason for LFF. In search for other factors affecting FF, recent studies showed a negative correlation between FF and IVF‐conception, elevated triglyceride levels, alanine transaminase levels and increased white blood cells 53–55 . It should be further investigated if systematic evaluation of these parameters would be useful in NIPT‐failures and if this would help the decision to perform a redraw or not.…”
Section: Discussionmentioning
confidence: 99%
“…In search for other factors affecting FF, recent studies showed a negative correlation between FF and IVF-conception, elevated triglyceride levels, alanine transaminase levels and increased white blood cells. [53][54][55] It should be further investigated if systematic evaluation of these parameters would be useful in NIPTfailures and if this would help the decision to perform a redraw or not. We did not observe increased IVF rates, the other parameters were not investigated.…”
Section: Low Fetal Fractionmentioning
confidence: 99%
“…[27][28][29] FF has been associated with many other biological factors, including low molecular weight heparin use, aspirin use, hypertension, pregestational diabetes, autoimmune disease, race, multiple gestation, smoking, conception, and white blood cell count. [30][31][32][33] At present, there is no consensus regarding how to manage patients at risk for low FF, other than counseling regarding the possibility of a failed test due to inadequate FF.…”
Section: Trisomies 13 and 18mentioning
confidence: 99%